Human relations in organizations : a skill-building approach - Lussier, Robert N. (Chicago : Irwin, 1996)
As the subtitle indicates, Lussier's Human Relations in Organizations: Applications and Skill Building employs a workbook-type approach. This approach is perfect for professors who want to incorporate activities and exercises into the classroom, and benefits students who want to understand concepts as well as apply and develop skills that they can use in their daily and professional lives. The book provides a balanced, three-pronged approach: a clear concise understanding of human relations/ organizational behavior concepts; the application of HR/OB concepts for critical thinking in the busine.
Includes bibliographical references (p. 537-548) and index.
Keywords: Organizational behavior; Interpersonal relations